Perancangan dan Pengembangan E-Catalog Ju Seafood Restaurant - Deli Deli; Hery Yanto (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Ju Seafood Restaurant is a small micro and medium enterprise which is engaged in culinary and seafood. The problems faced by Ju Seafood Restaurant are the lack of application of marketing strategies in their business and the use of social media as business support media is still not utilized properly. The method used to carry out practical work activities is divided into 2 stages: the data collection stage and the catalog creation stage. The result of this activity is an e-catalog which is implemented through a social media account, namely Instagram. The implementation of this practical work activity shows that the use of e-catalog has a very good influence on the business development of Ju Seafood Restaurant.